2011
DOI: 10.1369/0022155411428078
|View full text |Cite
|
Sign up to set email alerts
|

Host-Derived Pericytes and Sca-1+Cells Predominate in the MART-1Stroma Fraction of Experimentally Induced Melanoma

Abstract: Identification of cell types in tumor-associated stroma that are involved in the development of melanoma is hampered by their heterogeneity. The authors used flow cytometry and immunohistochemistry to demonstrate that anti–MART-1 antibodies can discriminate between melanoma and stroma cells. They investigated the cellular composition of the MART-1−, non-hematopoietic melanoma-associated stroma, finding it consisted mainly of Sca-1+ and CD146+ cells. These cell types were also observed in the skin and muscle ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…In addition, overexpression of HIF-1α promoted soft colony formation and invasion through Matrigel. Moreover, in a separate study, it was observed that increased HIF-1α expression was present not only in the melanoma cells but also in melanoma-associated stromal cells, including pericytes 42 . Finally, increased expression of HIF-1α and HIF-2α was found to be correlated with VEGF expression 43 .…”
Section: Introduction: Overview Of the Biology Of The Hypoxia-inducibmentioning
confidence: 87%
“…In addition, overexpression of HIF-1α promoted soft colony formation and invasion through Matrigel. Moreover, in a separate study, it was observed that increased HIF-1α expression was present not only in the melanoma cells but also in melanoma-associated stromal cells, including pericytes 42 . Finally, increased expression of HIF-1α and HIF-2α was found to be correlated with VEGF expression 43 .…”
Section: Introduction: Overview Of the Biology Of The Hypoxia-inducibmentioning
confidence: 87%
“…Moreover, tumour hypoxia has also been associated with enhanced expression of HIFs, lactate dehydrogenase 5 and autophagy‐related proteins, including beclin‐1 and light chain 3A (LC3A), in hypoxic melanoma cells that may promote anaerobic glycolysis and extensive autophagy activity and contribute to their survival under oxygen and nutrient deprivation . On the other hand, high level of HIF‐1α has also been detected in melanoma cells expressing melanoma antigen recognized by T cells‐1 MART‐1 + found in perivascular regions within tumour as well as MART‐1 − non‐haematopoietic melanoma‐associated stromal cells, including CD146 + pericytes associated with CD31 + endothelial cells and Sca‐1 + stromal cells in a mouse model of melanoma . This suggests that stromal cells and melanoma cells, which can form functional vessel‐like structures by vasculogenic mimicry, can cooperate for tumour vascularization supporting the interest to co‐target these cells to counteract melanoma development.…”
Section: Functions Of Hypoxia and Hifs In The Development Of Melanomamentioning
confidence: 99%
“…In normal cells, nucleolin is associated to the fibrillar components in nucleoli [ 24 ]. Immunocytochemistry labeling protocols were applied to cells seeded in Lab-Tek II 4-well chamber slides (Nalgen Nuc) [ 25 ]. After incubation, wells were washed from residual culture media with Dublecco’s Phosphate Buffered Saline (DPBS) and Tris-Buffered Saline solution with 0.1% Tween 20 (TBS-T), then fixed in 4% paraformaldehyde in PBS pH 7.2, freshly diluted from 16% paraformaldehyde, for 10 min at RT.…”
Section: Methodsmentioning
confidence: 99%